A cibersegurança na política externa e de segurança da Estónia - Silva, Ricardo Alexandre Marques (2020)
This thesis is focused on the role of Estonia's Foreign Policy in the field of cybersecurity. The concepts of cyberspace and cybersecurity are explored, detailing the main challenges that take place there, in order to better understand the threats faced by the advanced estonian digital society. It deals with the work of the main forums in which Estonia takes part, whose decisions and/or positions have a potential internal impact. In NATO and the EU, especially, this country finds a stage for its voices, drawing attention on the Russian geopolitical movements, which they see as hostile. The existence of a third-generation strategic vision in the field of cybersecurity allows it to have a central position in Estonia's Security Policy and Foreign Policy. It is intended to argue that Estonia is taking advantage of its talent in cybersecurity internationally, using it in order to preserve its broader national security.